A Different Way of Sitting: American Patent Folding Chairs of the 19th Century - Batley, Tania (Material Culture Review, 2012)
The 19th-century American parlour was the focus for social and economic signifiers for the emerging middle class. The evolving use of the parlour within the domestic interior, industrialization, and its impact on the role of middle-class women, coupled with design reform, created the ideal conditions for the acceptance of the patent folding chair into the American home. Patent folding chairs were placed at the centre of the home, valued for their functional and innovative design. Companies such as the New Haven Folding Chair Company of New Haven, Connecticut, E. W. Vaill Chair Company of Worcester, Massachusetts, and the Luburg Manufacturing Company of Philadelphia, Pennsylvania, created an endless diversity of patent folding and rocking chairs for the middle-class consumer. Adaptable, mobile, and functional, these chairs allowed a variety of postures to suit the consumer. As the market for patent folding chairs weakened, manufacturers found innovative ways to create new products for the middle class.